Turn-off failure mechanism in large area IGCTs - Lophitis, Neophytos; Antoniou, Marina; Udrea, Florin; Wikstrom, Tobias; Nistor, Iulian (My University, 2011)
The destruction mechanism in large area IGCTs (Integrated Gate Commutated Thyristors) under inductive switching conditions is analyzed in detail. The three-dimensional nature of the turn-off process in a 91mm diameter wafer is simulated with a two-dimensional representation. Simulation results show that the final destruction is caused by the uneven dynamic avalanche current distribution across the wafer. © 2011 IEEE.
Keywords: Integrated Gate Commutated Turn-off Thyristor; Large Area SOA